Therapeutic impact of human trophoblast stem cells in peritoneal and pneumonia-induced sepsis in mice - Narae Hwang; Gu Li; Ekaterina Murzin; Cassidy J. Mays; James A. Lederer; Xiaoli Liu; Mark A. Perrella (Stem Cell Research & Therapy)
Abstract Background Sepsis is a complex and life-threatening disease process related to a systemic response to severe infection. Due to the challenges of treating patients with sepsis, new therapies are being investigated, including cell-based approaches. Trophoblast stem cells (TSCs) are immune privileged cells with immunomodulatory properties. Thus, we proposed that TSCs may be beneficial in experimental models of sepsis to regulate the immune response and curtail organ injury. Methods Sepsis was induced by experimental models in mice; cecal ligation and puncture (CLP) and lung infection with Streptococcus (S.) pneumoniae. TSCs were isolated from the chorionic villi of human (h) term placentas, and from mouse (m) placentas using anti-CD117 MicroBeads, and were administered intravenously 6 h after CLP or S. pneumoniae infection. We assessed mortality, bacterial clearance, organ injury, inflammatory response, and production of cytokines and chemokines. Results CD117+ hTSCs did not express human leukocyte antigen (HLA) I or II, and were clonogenic and self-renewing. CLP led to severe mortality by 7 days, and administration of either hTSCs or mTSCs resulted in markedly improved survival compared with control cells or vehicle. hTSCs promoted bacterial clearance and decreased organ injury in the liver, kidney, spleen, and bowel. The elevated innate immune response in the peritoneum, predominantly neutrophils, was attenuated by hTSCs. In addition, neutrophil infiltration into the spleen was less in mice receiving hTSCs, which corresponded with reduced plasma pro-inflammatory cytokines and chemokines. When assessing the lung response to S. pneumoniae infection, administration of hTSCs resulted in fewer bacteria in bronchoalveolar lavage fluid (BALF) and lung tissue, and less lung edema and injury. Neutrophils, which were markedly increased in BALF, were diminished and infiltration of neutrophils and macrophages into the lungs was decreased by hTSCs. BALF pro-inflammatory cytokines and chemokines were mitigated by hTSCs to levels of Sham mice, and systemic injury to the liver and spleen was attenuated. Conclusions CD117+ hTSCs are immune privileged cells that when given after the onset of experimental models of infection/sepsis resulted in improved outcomes due to enhanced bacterial clearance, resolving inflammation, and less organ injury. These data support hTSCs as a potential cell-based therapy for sepsis.